ANALISIS PENGARUH HARGA DAN STORE ATMOSPHERE TERHADAP MINAT BELI ULANG DI KEDAI KULINER 27 GADING SERPONG - Kurniawan, Kevin; Sarudin, Rendy (Jurnal Ilmiah Global Education, 2023)
This study aims to analyze the relationship and determine the effect of price and store atmosphere on repurchase intention at Kedai Kuliner 27 Gading Serpong. The research uses quantitative methods by distributing questionnaires to the number of respondents according to the requirements of the research. Based on the research, it consists of 3 variables, namely variable X1, variable X2, and variable Y. The average value for variable X1 is 4.18 (High), X2 is 4.05 (High), while variable Y is 4.06 ( Tall). Based on the results of the T test, it obtained a significance value of 0.00, which means that the variables X1 (Price) and X2 (store atmosphere) have an effect on Y (Repurchase Intention). The Coefficient of Determination Test (R2) gets a value of 0.706. So, it can be concluded that variable Y can be explained by 71%.